2002
DOI: 10.1074/jbc.m112234200
|View full text |Cite
|
Sign up to set email alerts
|

α2-HS Glycoprotein/Fetuin, a Transforming Growth Factor-β/Bone Morphogenetic Protein Antagonist, Regulates Postnatal Bone Growth and Remodeling

Abstract: Soluble transforming growth factor-␤ (TGF-␤)/bone morphogenetic protein (BMP)-binding proteins are widely distributed in mammalian tissues and control cytokine access to membrane signaling receptors. The serum and bone-resident glycoprotein ␣2-HS-glycoprotein/fetuin (ASHG) binds to TGF-␤/BMP cytokines and blocks TGF-␤1 binding to cell surface receptors. Therefore, we examined bone growth and remodeling phenotypes in ASHG-deficient mice. The skeletal structure of Ahsg ؊/؊ mice appeared normal at birth, but abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
148
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(155 citation statements)
references
References 56 publications
4
148
1
2
Order By: Relevance
“…The IHC localization of fetuin-A in the mineralized areas of bone matrix has been already described in normal adult humans [28] and other mammals [29,30]. Our results show that the protein is highly represented in mineralized matrix of normal bone of uremic patients, as well as in any form of renal osteodystrophy, independent of the rate of bone turnover and of the type (lamellar or woven) of bone structure.…”
Section: Discussionsupporting
confidence: 74%
“…The IHC localization of fetuin-A in the mineralized areas of bone matrix has been already described in normal adult humans [28] and other mammals [29,30]. Our results show that the protein is highly represented in mineralized matrix of normal bone of uremic patients, as well as in any form of renal osteodystrophy, independent of the rate of bone turnover and of the type (lamellar or woven) of bone structure.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, it has been suggested that fetuin-A is a transforming growth factor-β type II receptor mimic and acts as an antagonist of TGF-β and TGF-β-related bone morphogenetic protein (BMP) activities (27). Multiple investigations of fetuin-A-deficient mice on various genetic backgrounds suggest that fetuin-A has a role as a systemically acting inhibitor of ectopic bone formation (28)(29)(30)(31). Bone lesions in prostate cancer are predominantly osteoblastic and cause a relative increase in bone deposition (32).…”
Section: Discussionmentioning
confidence: 99%
“…39 Fetuin A is also involved in the regulation of osteogenesis and bone resorption. 99 Clinical studies consistently show that fetuin-A deficiency is associated with vascular calcification and mortality in chronic kidney disease patients. Both chronic inflammation and uremia may contribute to fetuin-A depletion, 98 and low fetuin-A serum concentrations in hemodialysis patients are associated with severe extraosseous calcifications and highly increased cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%